Strategi Guru Pendidikan Agama Islam dalam Menanamkan Budaya Religius Pada Anak Berkebutuhan Khusus Tunarunggu di SLB Negeri 1 Kota Bengkulu - Sefty Monita Sari (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this study is to analyze (1) The strategy of Islamic Religious Education teachers in instilling religious culture in the State Special School 1 Bengkulu City. (2) The impact of deaf students’ behavior from the implementation of religious culture planting and (3) The influencing factors in the process of instilling religious culture in the State Special School 1 Bengkulu City. This type of research is descriptive qualitative using a phenomenological approach and a pedagogic approach. Techniques Data collection is done through observation, interviews and documentation. The results showed first, that the strategy of Islamic religious education teachers in instilling religious culture in the State Extraordinary School 1 Bengkulu City through the stages of planning, implementation and evaluation, in the process of instilling religious culture in deaf students was carried out using power strategies, refraction strategies and exemplary strategies used in the internalization process to deaf students. For the types of religious culture that are applied (1) Muslim attire, (2) smiling, greeting and greetings, (3) praying dzuhur in congregation and praying dhuha, (4) reading the Qur’an, (5) self-development and ( 6) infaq/sadaqa. Second, the impact of student behavior on the cultivation of religious culture can be seen in daily habits, namely (1) respect for teachers, (2) tolerance and (3) mutual cooperation. Third, the influencing factors in the process of instilling a religious culture consist of supporting factors, namely the cooperation of all teachers and the inhibiting factors, including facilities and infrastructure, parental participation, and language limitations.